Geopolitical and Security Concerns of the EU's Enlargement to the East: The Case of Ukraine, Moldova and Georgia - Tinatin Akhvlediani (Intereconomics, 2022)
Russia's unprovoked and unjustified full-scale invasion of Ukraine has significantly changed the geopolitical circumstances on the European continent and is also importantly reshaping the EU's enlargement policy.
Keywords: F51; F53; 330